Hybrid Propulsion Composition 2080 Technology as a Kamikaze Drone Power System Using Fire and Forget Simulation System - Muda, Nur Rachman Supadmana; Wellyanto, Mochammad Alif (Lembaga Pendidikan dan Penelitian Manggala Institute, 2025)
This study aims to examine the implementation of a hybrid propulsion system with a fuel composition of 20% solid and 80% liquid as the main power source in kamikaze drones with a remote control system as far as 280 km. Hybrid propulsion systems were chosen because they combine the advantages of a solid propulsion system that has a fast reaction time and a liquid propulsion system that provides better thrust control. In this study, the drone was designed using the fire and forget system method, which is an autonomous control system that does not require advanced control after launch. This method increases the effectiveness of attacks against both moving and static targets in long-range combat scenarios. The tests were carried out through simulations of aerodynamics, fuel efficiency, and analysis of the performance of the control system in various operational scenarios. The results showed that the propulsion composition of 20-80 provided optimal thrust efficiency as well as stability of the flight direction, with a success rate of 92% in long-range mission simulations. As such, the system has the potential to be a strategic alternative in the development of high-performance, high-precision kamikaze drones.